Coherent control of complex conductivity in a conductive atomic medium. (28th May 2021) - Ali, Sajid; Ur Rahman, Amin; Amin Bacha, Bakht; Ullah, Arif; Ul Haq, Imran
Abstract: The conductivity of a conductive atomic medium is controlled and modified by the strength and detuning of the control fields. At the probe resonance point the value of conductivity is measured to 500 S m −1 and at the control field resonance point the value of conductivity is measured to 600 S m −1 . High value of conductivity is reported at the resonance points of the probe as well as the control field. At low decay and low intensity of the control field the value of conductivity is high, while contrast behaviors are also true. The significant modification in the value of complex conductivity may be useful for forward and backward emf-generation.